PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM PELANGGARAN REKLAMASI TAMBANG BATUBARA: PROBLEMATIKA DAN IMPLIKASINYA TERHADAP KERUSAKAN JALAN - Yusuf Eka Nur Prasetya; Haris Retno Susmiyati; Orin Gusta Andini (Universitas Labuhanbatu, 2026)
Coal mining activities in Indonesia are legally required to conduct post-mining reclamation as part of environmental and social responsibility. However, in practice, violations of reclamation obligations remain prevalent, leading to damage to public infrastructure, including roads affected by unreclaimed mining pits. This study aims to analyze corporate criminal liability in violations of coal mine reclamation obligations and their implications for road damage. The research employs an empirical approach using a socio-legal method, with purposive sampling to select informants, and data collection conducted through interviews, observations, and literature review. The findings indicate that corporate entities have failed to fulfill their reclamation obligations, resulting in direct impacts on public road infrastructure. Furthermore, significant challenges in law enforcement were identified, including weak supervision by mining inspectors and the lack of firm action by law enforcement authorities. These conditions demonstrate that corporate criminal liability has not been effectively enforced in practice. This study highlights the necessity of strengthening regulatory oversight, enforcing stricter legal measures, and ensuring the effective implementation of corporate criminal liability to prevent environmental degradation and infrastructure damage caused by mining activities. From a theoretical perspective, this research contributes to the development of corporate criminal liability discourse in environmental law by emphasizing the linkage between regulatory compliance and public infrastructure protection.Keywords: Coal Mining, Corporate Criminal Liability, Reclamation, Road Damage, Law Enforcement